The performance of gross pollutant trap for water quality preservation: a real practical application at the Klang Valley, Malaysia - Sidek L.; Basri H.; Lee L.K.; Foo K.Y. (Taylor and Francis Inc., 2023)
catchment; pollutant removal; river pollution; river water; stormwater; water chemistry; water quality; Klang Valley; Malaysia; West Malaysia